2020
DOI: 10.1016/j.brs.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal transcranial direct-current stimulation improves early technical skills in surgery

Abstract: Background: Studies applying transcranial direct-current stimulation (tDCS) to motor regions to enhance surgical skills have observed modest benefits in performance. Early surgical skills acquisition is known to be dependent on the prefrontal cortex (PFC) which could be a suitable target for performance enhancement in fields with high cognitive demand. Objective: To assess whether prefrontal tDCS could improve early phases of surgical skill development. Methods: In a randomized sham-controlled double-blind par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 58 publications
(60 reference statements)
3
36
0
Order By: Relevance
“…Among them, six were excluded because they did not fulfill the inclusion criteria (Table S3). Therefore, six articles were retained for the current meta-analysis (Table 1) [9,10,21,22,37,38]. Across the 6 eligible RCTs, a total of 198 participants with a mean age of 23.7 years (range 21.6-25.7) and a female proportion of 62.6% (range 46.7-72.7) were included.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, six were excluded because they did not fulfill the inclusion criteria (Table S3). Therefore, six articles were retained for the current meta-analysis (Table 1) [9,10,21,22,37,38]. Across the 6 eligible RCTs, a total of 198 participants with a mean age of 23.7 years (range 21.6-25.7) and a female proportion of 62.6% (range 46.7-72.7) were included.…”
Section: Study Selectionmentioning
confidence: 99%
“…Across the 6 eligible RCTs, a total of 198 participants with a mean age of 23.7 years (range 21.6-25.7) and a female proportion of 62.6% (range 46.7-72.7) were included. Among these six eligible RCTs, three investigated the efficacy of anodal tDCS over dominant primary motor cortex/cathodal tDCS over contralateral hemisphere surrounding F3/F4 for 20 min [9,10,21], one investigated the efficacy of cathodal tDCS over right primary motor cortex (M1) stimulation and anode over left primary motor cortex (M1) [22], one investigated the efficacy of tDCS without detailed information about the specific polarity over prefrontal cortex stimulation [37], one investigated anodal tDCS over left dorsolateral prefrontal cortex (DLPFC) (F3) and cathodal tDCS over right DLPFC (F4) [38], and one investigated the efficacy of tDCS over supplementary motor area stimulation (the anode over Cz and the cathode over Fpz) [22]. All the tDCS stimulation had been applied during their initial training session.…”
Section: Study Selectionmentioning
confidence: 99%
“…Emerging evidence suggests that transcranial direct-current stimulation (tDCS) improves laparoscopic skills and neurosurgical performance [2e5]. Similarly, performance scores on complex surgical bimanual tasks improve with tDCS when compared to sham [6]. Although these observations are encouraging, a number of important questions will resonate amongst both patients and surgeons surrounding safety, acceptability and the ethical concerns [7].…”
Section: Dear Editormentioning
confidence: 99%
“…The dataset reported here was collected from a double-blind randomized sham-controlled trial investigating the performance enhancing effects of prefrontal transcranial direct-current stimulation (tDCS) on surgical knot-tying performance [7] . The raw data can be found at DOI: 10.14469/hpc/7891 .…”
Section: Data Descriptionmentioning
confidence: 99%
“…However, extensive prior research has revealed an important role of the prefrontal cortex in surgical skill development [5 , 6] . This article presents the data of a double-blind randomized sham-controlled trial investigating the effect of prefrontal tDCS on knot-tying performance [7] . Data was collected from an active ( n = 20) and sham ( n = 20) group across three blocks: pre-, online- (during) and post-tDCS.…”
mentioning
confidence: 99%